Analysis of Factors Affecting The Success of Business Performance in Leading Products of Micro and Small Medium Enterprises in Central Java - Fathul Aminudin Aziz; Hastin Tri Utami (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2021)
Purpose: This study aims to determine the internal factors and external factors that influence the success of Micro and Small Medium Enterprises’s business performance of leading products in Central Java. Respondents in this study were 181 MSMEs delivered from various regencies in Central Java Province. Methodology: Hypothesis testing conducted by performing multiple linear regression tests with SPSS 25 for windows. Main Findings: The results of the study showed that internal factors: human resources, the use of accounting information and the use of information technology had a significant positive effect on the success of business performance and external factors which are government support and the business climate also had a significant positive effect on the success of business performance. Implication: The future studies could be more specialized in the types of MSMEs such as: business food, batik or handicraft so that the research results can be compared. Further research can also add both internal or external variables such as owner knowledge, business age, business scale or competitiveness. Future studies can also use other variables as moderating or intervening variables. Novelty/Originality of this Study: To date, there are no studies that examine internal factors (the ability of human resources, the use of accounting information and the use of information technology) and external factors (government support and business climate) affecting the success of business performance in leading products of micro and small medium enterprises in central java